Contribuição ao estudo do crânio de Placosoma Tschudi, 1847 (Sauria: Teiidae: Gymnophthalminae) - Soares, Marcelo de Araujo (1993)
The present study deals with the cranial osteology of Placosoma Tschudi, 1847 (Sauria, Teiidae, Gymnophthalminae), comparing the cranium of different species. For this study, was used the methods of Taylor and Van Dyke (1985), for clearing and staining the skulls, as well as other techniques. Detailed descriptions of cranial osteology of Placosoma are here emphasized, and measures of total length and width of the cranium are presented. Some cranial muscles and their bone insertion are mentioned. In the comparative osteological study of the Placosoma species, some differences were observed and analized from point of view of morphology and proportion of bones. The penetration of the nasal process of maxilla in the nasal bones, the suture of postfrontal with postorbital and frontal, the shape and number of teeth on the maxilla and dentary, among others, are emphasized.